“We’re one small piece of the puzzle”: evaluating the impact of short-term funding for tier two weight management services - Beaumont, Jordan D.; Ioannou, Elysa; Harish, Krishna; Elewendu, Nnedinma; Corrigan, Nicola; Nield, Lucie (Frontiers in Public Health, 2024)
Introduction Overweight and obesity are a global health epidemic and many attempts have been made to address the rising prevalence. In March 2021 the UK government announced £100 million of additional funding for weight management provisions. Of this, £30.5 million was split across local authorities in England to support the expansion of tier two behavioural weight management services for adults. The present work aimed to explore how this funding was used within the Yorkshire and Humber region to consolidate learning, collate best practice, and provide recommendations for future funding use. Method One-hour semi-structured interviews were conducted with 11 weight management service commissioners representing 9 of the 15 local authorities in the region. Interviews were recorded, transcribed and analysed using an established health inequality framework. From this, recommendations were co-developed with the commissioner group to establish best practice for future funding use. Results Commissioners recognised that targeted weight management services were only one small piece of the puzzle for effectively managing obesity. Therefore, recommendations include targeting underserved communities, focussing on early prevention, addressing weight management in a whole systems context, and embracing innovative and holistic approaches to weight management. Discussion Current short-term funding and restrictive commissioning processes of tier two services prevents sustainable and innovative weight management practice which is detrimental to patients, falls short of addressing health inequalities and negatively impacts staff health and wellbeing.